Birds in the ‘Burbs’: Do migratory birds prefer urban forest fragments or residential yards? - Ryan Byron; Mark Hostetler; Michael Andreu (EDIS)
During migration, birds travel from their northern breeding grounds to their southern wintering grounds and vice versa. To understand which urban habitats are valuable for specific migratory species, we compared the diversity of migratory bird species that used urban forest fragments vs residential areas with tree canopy in Gainesville, Florida. Study results summarized in this fact sheet can help inform urban planners, developers, and homeowners about vegetation migratory birds use. Conservation of large, forested areas is important, but fragmented landscapes are not useless, and conserving urban forest fragments and trees in residential areas is also important for bird conservation.